MANAGEMENT OF PREPARTUM CERVICO VAGINAL PROLAPSE IN I COWS WITH INDIAN MALLOW AND CASTOR OIL - DEVI, U UMA; UMAKANTHAN, T (The Indian Journal of Animal Reproduction, 2011)
Recurrent Pre-parturn prolapse was successfully managed with Abutilon indicum and Ricinus communis incows.
Keywords: Genital; Prolapsed; Ricinus communis; Abutilon indicum